Penentukuran model graviti untuk corak perjalanan kenderaan perdagangan di Lembah Klang - Riza Atiq Abdullah O.K. Rahmat,; Mohd. Soflan Asmirza. S,; Amiruddin Ismail, (1998)
This study involves the analysis of commercial vehicles trip patterns in Klang Valley using the Gravity Model which are singly and doubly constrained. For every type of the Gravity Model, distance and travel time were adopted as the spatial separation between the transport zones. The models were calibrated using observed origindestination trip matrices of commerciul vans, lorries, trailer-lorries and trailercontainer- lorries. This study demonstrated that doubly-constrained Gravity Model synthesised the trip patterns more accurately forr both types of the spatial separation. Trailer-lorries and container-lorries trip patterns are synthesised more accurately using the travel time as the separation function. Unlike for other types of vehicles, travel distance as the separation function in the Gravity Model synthesised more accurately the trip patterns. In term of separation function, both the single and doubly-constrained Gravity Models using power function were found to be better than the exponential function for the three groups of vehicle i.e. heavy lorries, trailerlorries and container-lorries. However the exponential function is better in replicating the trip patterns of commercial vans and small lorries as this type of vehicles are usually used for short distance hauling